Fiscal Illusion and Asymmetric Response of Regional Financial Performance - Marthen Anthon Pentury; Lillyani Margaretha Orisu; Martha A.C. Kareth (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Purpose of this research is to prove whether there is a fiscal illusion in the regional financial performance of districts/cities in West Papua and to capture asymmetric response of regional spending. Period in this research from 2010-2019 in West Papua Province which consists of nine districts/cities considering the availability of data, data sources from the Central Statistics Agency (BPS) and the Ministry of Finance (KEMENKEU) Dependent variable is regional financial performance as measured by regional spending and independent variable consists of general allocation funds, special autonomy funds, regional gross domestic product, population, local taxes, local retribution and dummy variables. Analysis methods is panel data regression fixed effect approach, fiscal illusion detection refers to the model developed by Borcherding and Deacon, and response asymmetry refers to the Gennari and Messina model. Findings/Originality: Proving the existence of fiscal illusions and asymmetry responses in a panel data model, results show that there are fiscal illusions in the regional financial performance of districts/cities in West Papua Province as seen from the negative and significant correlation of regional spending with local taxes. There is an asymmetrical response to regional spending in increasing the balancing fund, seen from the negative and significant dummy variable value in the model.